2010
DOI: 10.1128/jb.00847-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pgp3, aChlamydia trachomatisPlasmid-Encoded Immunodominant Antigen

Abstract: Human antibody recognition of Chlamydia trachomatis plasmid-encoded Pgp3 protein is dependent on the native conformation of Pgp3. The structural basis for the conformation dependence and the function of Pgp3 remain unknown. Here, we report that Pgp3 trimerization is required for the recognition of Pgp3 by human antibodies. In a native polyacrylamide gel, Pgp3 purified from a bacterial expression system migrated as stable trimers that were dissociated into monomers only by treatment with urea or sodium dodecyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 44 publications
4
73
0
Order By: Relevance
“…In some experiments, the GST-fusion proteins bound to the glutathione-agarose beads were used to absorb the antibodies for confirming the antibody specificities. Production of various control GST-fusion proteins, including GST-CPAF (a chlamydia-secreted serine protease [10]), GST-Pgp3 (a chlamydial plasmid-encoded outer membrane and secretion protein [6,24]), GST-cHSP60 (chlamydial HSP60), and GST-MOMP (the chlamydial major outer membrane protein from serovar D) have been described elsewhere (36).…”
Section: Methodsmentioning
confidence: 99%
“…In some experiments, the GST-fusion proteins bound to the glutathione-agarose beads were used to absorb the antibodies for confirming the antibody specificities. Production of various control GST-fusion proteins, including GST-CPAF (a chlamydia-secreted serine protease [10]), GST-Pgp3 (a chlamydial plasmid-encoded outer membrane and secretion protein [6,24]), GST-cHSP60 (chlamydial HSP60), and GST-MOMP (the chlamydial major outer membrane protein from serovar D) have been described elsewhere (36).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, some of the chlamydial antigens that trafficked to the ER were seen to co-localize with the MHC-like molecule CD1d (see below) (Wyrick 2010). Others have shown that proteins such as the chlamydial outer membrane complex protein B (OmcB) (Qi, Gong et al 2011) and the chlamydia protease, CPAF (see below), are present in the host cell cytosol (Sharma, Bosnic et al 2004;Kawana, Quayle et al 2007), the latter being secreted through a Sec-dependent pathway (Chen, Lei et al 2010). C. trachomatis also uses the type III secretory system (T3SS) to move bacterial virulence proteins from EB into the host cytosol (Clifton, Fields et al 2004;Hower, Wolf et al 2009).…”
Section: Pathogen Immune Evasionmentioning
confidence: 99%
“…Many virulence factor candidates have been identified, such as the polymorphic outer membrane autotransporter family of proteins [11,12], the putative large cytotoxin [13], stress response proteins [14], and chlamydial secretion effectors [15][16][17]. It is known that C. trachomatis organisms can secrete numerous proteins into host cell cytoplasm [18,19]. Among them, Chlamydial Protease-Like Activity Factor (CPAF), a chlamydial type II secretion protein, may serve as a promising candidate of virulence factor as proposed [16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%